2017
DOI: 10.1080/14786419.2017.1375915
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive coumarins from the roots and fruits of Ferulago trifida Boiss., an endemic species to Iran

Abstract: Phytochemical analysis of the Ferulago trifida Boiss. from Apiaceae family led to the isolation and identification of suberosin (1), isoimperatorin (2), prantschimgin (3), oxypeucedanin (4), oxypeucedanin methanolate (5), suberenol (6), 6-hydroxymethylherniarin (7), oxypeucedanin hydrate (8), ulopterol (9), bergapten (10), xanthotoxin (11), imperatorin (12) and grandivittin (13) from chloroform extracts of the roots (1-9) and fruits (1, 2, 8, 10-13) of this species. Oxypeucedanin methanolate and suberenol demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 16 publications
(3 reference statements)
0
13
0
1
Order By: Relevance
“…The bioactivities of the extract of aerial parts and of the EO have been previously studied. For instance, different extracts and coumarins of the plant exerted moderate antiradical scavenging, antibacterial, and antioxidant activities . Moreover, in the literature antioxidant activity, in vivo anxiolytic and antidepressant for the EO, along with cytotoxicity, apoptosis‐inducing, and in vitro anticancer effects of the extracts were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactivities of the extract of aerial parts and of the EO have been previously studied. For instance, different extracts and coumarins of the plant exerted moderate antiradical scavenging, antibacterial, and antioxidant activities . Moreover, in the literature antioxidant activity, in vivo anxiolytic and antidepressant for the EO, along with cytotoxicity, apoptosis‐inducing, and in vitro anticancer effects of the extracts were reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, different extracts and coumarins of the plant exerted moderate antiradical scavenging, [15][16][17][18] antibacterial, [19] and antioxidant activities. [20] Moreover, in the literature antioxidant activity, [4,7,10,21 -25] in vivo anxiolytic and antidepressant for the EO, [4] along with cytotoxicity, apoptosis-inducing, [16] and in vitro anticancer effects [26] of the extracts were reported. Furthermore, the AcOEt and methanolic extract of F. angulata previously revealed the highest levels of phenolic compounds among its various extracts.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Tavakoli et al reported the isolation of thirteen coumarin derivatives from the roots and fruits of Ferulago trifida, among them suberosin showed higher preferential toxicity against MDA-MB-23 cells (IC 50 : 0.21 mM, Selectivity index: 5.0), in comparison with tamoxifen (IC 50 : Pharmaceutical Sciences, 2021, 27(1), 139-146 | 143 0.012 mM, Selectivity index: 2.45) and strong antibacterial activity against S. epidermidis (Inhibition zone; 19 mm, MIC; 250 μg/ml). 25 In the mentioned study, suberenol was also found as a potent antioxidant in ferric reducing antioxidant power (FRAP) test (251.2 ± 6.2 mmol FSE/100 g). 25 In another study, phytochemical analysis of Ferulago bracteata roots using a bioassay guided approach resulted in the isolation of suberosin, bergapten, imperatorin, and other nine compounds, of which suberosin showed the potent α-glucosidase inhibitory activity (IC 50 : 0.89 mg/ ml) in comparison with reference standard acarbose (IC 50 4.95 mg/ml).…”
Section: Resultsmentioning
confidence: 84%
“…25 In the mentioned study, suberenol was also found as a potent antioxidant in ferric reducing antioxidant power (FRAP) test (251.2 ± 6.2 mmol FSE/100 g). 25 In another study, phytochemical analysis of Ferulago bracteata roots using a bioassay guided approach resulted in the isolation of suberosin, bergapten, imperatorin, and other nine compounds, of which suberosin showed the potent α-glucosidase inhibitory activity (IC 50 : 0.89 mg/ ml) in comparison with reference standard acarbose (IC 50 4.95 mg/ml). 31 Anti-inflammatory potential of suberosin, a major prenylated coumarin isolated from F. angulata fruits, has been demonstrated by its inhibitory effects of proliferation of human peripheral blood mononuclear cells (HPBC) proliferation through reduction of intracellular Ca 2+ concentration and inhibition of ERK, NF-AT, and NF-κB activation.…”
Section: Resultsmentioning
confidence: 84%
“…However, these compounds did not seem to be active against 4 bacterial strains (S. typhimurium, K. pneumonia, E. faecalis and P. mirabilis). The antimicrobial properties of several furanocoumarins have been reported previously, for Bergapten isolated from Treculia obovoidea (Kuete et al, 2007) and for Isoimperatorin isolated from the roots and fruits of Ferulago trifida Boiss (Tavakoli et al, 2018). and isopimpinellin isolated from Prangos uloptera roots (Razavi et al, 2009) and from Peucedanum zenkeri seeds (Ngwendson et al, 2003).…”
Section: Antibacterial Activitymentioning
confidence: 72%